What is the following sum? Assume x > 0 and y > 0 sqrt x^2y^2+2 sqrt x^3y^4+xy sqrt y

Question

What is the following sum? Assume x > 0 and y > 0 sqrt x^2y^2+2 sqrt x^3y^4+xy sqrt y

in progress 0
Emery 2 weeks 2021-09-13T15:11:12+00:00 2 Answers 0

Answers ( )

    0
    2021-09-13T15:12:45+00:00

    Answer:

    xy(1+2y\sqrt{x}+\sqrt{y})

    Step-by-step explanation:

    Given expression,

    \sqrt{x^2y^2}+2\sqrt{x^3y^4}+xy\sqrt{y}

    =(x^2y^2)^\frac{1}{2} + 2(x^3y^4)^\frac{1}{2} + xy\sqrt{y}

    \because (\sqrt{x}=x^\frac{1}{2})

    =(x^2)^\frac{1}{2} (y^2)^\frac{1}{2} + 2(x^3)^\frac{1}{2} (y^4)^\frac{1}{2} + xy\sqrt{y}

    (\because (ab)^n=a^n b^n)

    =x^{2\times \frac{1}{2}} y^{2\times \frac{1}{2}} + 2(x^{3\times \frac{1}{2}})(y^{4\times \frac{1}{2}})+xy\sqrt{y}

    \because (a^n)^m=a^{mn}

    =x^1 y^1 + 2x^{1\frac{1}{2}} y^2 + xy\sqrt{y}

    =xy+2x.(x)^\frac{1}{2} y^2 + xy\sqrt{y}

    =xy+2xy^2\sqrt{x}+xy\sqrt{y}

    =xy(1+2y\sqrt{x}+\sqrt{y})

    0
    2021-09-13T15:12:58+00:00

    Answer:

    B is the right option

    Step-by-step explanation:

    On edg :))

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )